Transformacja systemowa bylej NRD - oczekiwania a rzeczywistosc. Oceny procesu w literaturze niemieckiej - Michal Moszynski (Institute of Economic Research (IER), 2012)
– In this paper an attempt is made to outline the views on the transformation of the former GDR formulated in the German scientific literature. Due to the limited scope of the paper and the magnitude and complexity of the phenomena, discussion is limited to the most important and most controversial - according to the author - aspects around which discussions were held between leading economists from academia and politicians. The study starts with a brief introduction regarding the merits of the transformation of the economic order of the former GDR. Further outlines early assessments of the economic condition of Eastern Germany and ideas on eventual reunification of the country. Then, following, if possible, the chronological order, an overview is provided of the most important assessment about elements of a new order, such as the monetary union and the deregulation of prices, changes in the ownership structure, the creation of the institutional framework and the situation on the labor market and financial transfers. The main scientific method applied is analysis of literature, evaluation of official documents and historical analysis.
Keywords: B52; N14; P20; P30; 330; institutional economics; effectiveness of institutional system; TOPSIS method; global knowledge-based economy; European Union